PENDAMPINGAN PEMBELAJARAN BAHASA ARAB DI TPQ WONOGIRI - Fajarwati Kusuma Adi; Titik Vitriani; Muhammad Daqok (LPPM STAIMAS WONOGIRI, 2021)
Arabic and the Qur'an are a unit that complements each other, so that they are related to each other. If you master Arabic, it can be identified with mastery of the Qur'an, because the language used in the Qur'an is Arabic. If we study Arabic and the Qur'an, it is hoped that it can increase our devotion to Allah SWT, because this is also contained in the prayer and prayer guidelines used. In accordance with Article 31 of the Basic Law concerning Education that every citizen has the right to formal and non-formal education, this is obtained through learning at school and outside school. In mentoring the TPQ (Al-qur'an Education Park) in Wonogiri is included in the non-formal category because the way of learning is outside school hours. The method used in this service is a qualitative descriptive method supported by laws, books, journals and the internet. By taking samples for the implementation of activities, Arabic language learning assistance and interviews with Arabic language teachers or teachers at TPQ (Al-qur'an Education Park) and students who are studying and people who send their children to school in the TPQ (Al-qur'an Educational Park) institution. an), The assistance that the author provides has implications in the form of input in educating children in learning Arabic, as well as improving the quality of religion from an early age in the living environment and filling positive activities to increase knowledge and faith.